SRAP markers for characterization of the genetic diversity and differentiation of Pinus nigra populations in protected forested areas in Bulgaria, Greece, and Cyprus - Zagorcheva, Tzvetelina; Rusanov, Krasimir; Bosmali, Eirini; Savvides, Andreas; Madesis, Panagiotis; Fotopoulos, Vasileios; Rusanova, Mila; Ustabashiev, Filip; Atanassov, Ivan I. (My University, 2024)
The present study aimed to evaluate the genetic diversity and differentiation of Pinus nigra Arnold, the European black pine, populations located in protected forested areas in three countries from the Balkan and Mediterranean region: Bulgaria, Greece, and Cyprus. Totally, 175 DNA samples from P. nigra plants collected from eight populations in these countries were analyzed using three SRAP primer pairs. The applied SRAP markers demonstrated high-resolution power, resulting in the identification of an average of 215 ± 67 polymorphic loci per SRAP primer pair. The analysis of molecular variance (AMOVA) showed that 82% of the observed variation was due to intra-population variation, while 18% was due to inter-population variation. The overall analysis of the population structure suggested low (Fst ≤ 0.01) intra-country differentiation for the populations from Bulgaria and Cyprus and moderate (0.15 ≤ Fst ≤ 0.17) inter-country differentiation. On the contrary, high differentiation between the populations (0.06 ≤ Fst ≤ 0.20) and complex genetic structure were characteristic of the three populations from Greece, relatively closely located in the area of the Pindos National Park. Analysis of the population structure also revealed that one of the Pindos populations belonged to the cluster of Bulgarian populations (Fst ≤ 0.01), showing moderate (Fst ≤ 0.11) to high (Fst ≤ 0.20) genetic differentiation from the other analyzed Pindos populations. The further use of SRAP markers for mapping the genetic diversity among P. nigra populations and identification of local populations diverted from the overall phylogeography-driven pattern in the studied region are discussed.
Keywords: European black pine; mapping genetic diversity; Pinus nigra arnold; population structure; SRAP markers